Lexicality effects on orthographic learning in beginning and advanced readers of Dutch: An eye-tracking study. Issue 6 (June 2022) - van Viersen, Sietske; Protopapas, Athanassios; Georgiou, George K; Parrila, Rauno; Ziaka, Laoura; de Jong, Peter F
Orthographic learning is the topic of many recent studies about reading, but much is still unknown about conditions that affect orthographic learning and their influence on reading fluency development over time. This study investigated lexicality effects on orthographic learning in beginning and relatively advanced readers of Dutch. Eye movements of 131 children in Grades 2 and 5 were monitored during an orthographic learning task. Children read sentences containing pseudowords or low-frequency real words that varied in number of exposures. We examined both offline learning outcomes (i.e., orthographic choice and spelling dictation) of target items and online gaze durations on target words. The results showed general effects of exposure, lexicality, and reading-skill level. Also, a two-way interaction was found between the number of exposures and lexicality when detailed orthographic representations were required, consistent with a larger overall effect of exposure on learning the spellings of pseudowords. Moreover, lexicality and reading-skill level were found to affect the learning rate across exposures based on a decrease in gaze durations, indicating a larger learning effect for pseudowords in Grade 5 children. Yet, further interactions between exposure and reading-skill level were not present, indicating largely similar learning curves for beginning and advanced readers. We concluded that the reading system of more advanced readers may cope somewhat better with words varying in lexicality, but is not more efficient than that of beginning readers in building up orthographic knowledge of specific words across repeated exposures.